Socioeconomic benefits associated with bats - Siya Aggrey; Innocent B. Rwego; Eric Sande; Joyce D. Khayiyi; Robert M. Kityo; Charles Masembe; Rebekah C. Kading (BMC, 2024)
Abstract Background While bats are tremendously important to global ecosystems, they have been and continue to be threatened by loss of habitat, food, or roosts, pollution, bat diseases, hunting and killing. Some bat species have also been implicated in the transmission of infectious disease agents to humans. While One Health efforts have been ramped up recently to educate and protect human and bat health, such initiatives have been limited by lack of adequate data on the pathways to ensure their support. For instance, data on the role of bats in supporting different components of human welfare assets would be utilized as a stepping stone to champion conservation campaigns. Unfortunately, these data are limited and efforts to synthesize existing literature have majorly focused on few components human welfare leaving other important aspects. Methods Here, we analyze benefits associated with bats in the context of welfare economics considering all the asset components. We surveyed scientific and gray literature platforms utilizing particular keywords. We then classified these values using integrated approaches to understand different values across human welfare assets of "health," "material and immaterial assets," "security or safety" and "social or cultural or spiritual relations". Results We found 235 papers from different countries indicating that bats play fundamental roles in supporting human welfare. These benefits were more prevalent in Asia and Africa. In terms of the use of bats to support welfare assets, bats were majorly utilized to derive material and immaterial benefits (n = 115), e.g., food and income. This was followed by their use in addressing health challenges (n = 99), e.g., treatment of ailments. There was a similarity in the benefits across different regions and countries. Conclusion These results indicate potential opportunities for strengthening bat conservation programs. We recommend more primary studies to enhance understanding of these benefits as well as their effectiveness in deriving the perceived outcomes.